Dynamic Tests of a Large-Scale Three-Story RC Structure with Masonry Infill Walls. Issue 11 (1st November 2020) - Guljaš, Ivica; Penava, Davorin; Laughery, Lucas; Pujol, Santiago
ABSTRACT: RC buildings with masonry infill walls are common throughout the world. There is uncertainty about the effect of the infill walls on the response of the building to earthquake demands. To shed light on this issue, a three-story, scaled reinforced concrete frame with masonry infill walls was subjected to two sequences of base motions in two series of tests. In Series 1, hollow masonry units were used. After completion of this series, the structure was repaired by replacing hollow masonry units with new solid units. Reinforced concrete confining elements were also added along the vertical edges of window and door openings in the first and second stories. The repaired structure was then tested with the same sequence of base motions in Series 2. On average, drift demands were 30% smaller in Series 2 and were nearly half what the drift demands were estimated to be for the bare RC frame alone. These results support the hypothesis that masonry infill panels can be used to control drift in low-rise structures, provided they do not cause column failures and provided they are restrained from out-of-plane collapse. Projections made based on the test results also support the idea that a Wall Index (ratio of masonry wall density to ten times the number of stories) exceeding 0.2% leads to acceptable earthquake response in low-rise buildings.